Answer
a)
As t increases, x and y increase.
b)
$y=(x+1)^{3}+1$
![](https://gradesaver.s3.amazonaws.com/uploads/solution/a9916519-7b2e-4a83-bdca-49054117c423/result_image/1513147244.png?X-Amz-Algorithm=AWS4-HMAC-SHA256&X-Amz-Credential=AKIAJVAXHCSURVZEX5QQ%2F20250215%2Fus-east-1%2Fs3%2Faws4_request&X-Amz-Date=20250215T145224Z&X-Amz-Expires=900&X-Amz-SignedHeaders=host&X-Amz-Signature=d45802943bb21b664faff925f76fd71364d997a23158d39aea9ab7057df841b6)
Work Step by Step
a)
$x=t-1$
$y=t^{3}+1$
$-2 \leq t \leq 2$
When,
t=-2 x=-3 y=-7
t=-1 x=-2 y=0
t=0 x=-1 y=1
t=1 x=0 y=2
t=2 x=1 y=9
b)
$x=t-1$
$x+1=t$
$y=t^{3}+1$
$y=(x+1)^{3}+1$